Restoring Forest With High Density Plantation Method in Medchal District in Telangana State - Reddy, K. Srinivas; Reddy, A. Vijaya Bhasker; Reddy, P. Sathi (Indian Forester, 2022)
A study was conducted to find the performance of tree species under Miyawaki method of planting in Chengicherla Range Forest and Rachakonda Commssionarate Range Forest in Medchal District of Telangana State. The plantation was taken up during 2016. Thirty fast growing trees namely Tectona grandis, Pterocarpus santalinus, Bambusa vulgaris, Bombax ceiba, Peltophorum pterocar, Delonix regiapum and medium canopy species are Grevillea robusta, Phyllanthus emblica, Pongamia pinnata, Delonix regia, Tecoma stans, Bauhinia acuminata, Punica granatum, Limonia acidissima and Low canopy Species. Ocimum tenuiflorum, Acalypha hispida, Lawsonia inermi, Caesalpinia pulcherrima, Bauhinia variegata, Murraya koenigii, Bougainvillea glabra, Gliricidia sepium respectively are found highly suitable for afforestation in wastelands and also for urban forest. The unexpected natural disasters such as flood, drought, rise in sea level, could affect not only the community but ecology of the region also. The change in climate has adverse effects on food chains, plant, and animal habitats. For addressing climate variations, restoring forest ecosystems and recreating forests could be better solution. Because historical deforestation and degradation of natural resources resulted in a high density of wild plant species and the construction of forests might take many years, the concept of creating green cover in a shorter period of time is gaining traction across continents.